2023
DOI: 10.2196/37225
|View full text |Cite|
|
Sign up to set email alerts
|

Digital Phenotyping for Differential Diagnosis of Major Depressive Episode: Narrative Review

Abstract: Background Major depressive episode (MDE) is a common clinical syndrome. It can be found in different pathologies such as major depressive disorder (MDD), bipolar disorder (BD), posttraumatic stress disorder (PTSD), or even occur in the context of psychological trauma. However, only 1 syndrome is described in international classifications (Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition [DSM-5]/International Classification of Diseases 11th Revision [ICD-11]), which do not take … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 128 publications
0
7
0
Order By: Relevance
“…Digital phenotyping is the continuous monitoring of behavioral and mental states through user data tracking [ 66 ]. It provides objective measurements to improve disease classification, especially for trans-diagnostic symptoms.…”
Section: Asynchronous Technologies In Clinical Carementioning
confidence: 99%
See 1 more Smart Citation
“…Digital phenotyping is the continuous monitoring of behavioral and mental states through user data tracking [ 66 ]. It provides objective measurements to improve disease classification, especially for trans-diagnostic symptoms.…”
Section: Asynchronous Technologies In Clinical Carementioning
confidence: 99%
“…Another study suggested that markers such as automated voice analysis, video behavior analysis, and physiological measures that include heart rate variability and electrodermal activity studies could aid in forming differential diagnoses for major depressive episodes. Although comparative studies are lacking, promising results were found in digital markers with physiological measures, such as heart rate variability, which showed significant differences in patients with bipolar depression compared to unipolar depression and more reactivity in patients with comorbid post-traumatic stress disorder in major depressive disorder when being reminded about a psychological trauma [ 66 ].…”
Section: Asynchronous Technologies In Clinical Carementioning
confidence: 99%
“…This nding is notable for two reasons. First, it highlights that electrodermal activity abnormalities are core pathological features in the affective disorders 15,16,33 . Second, the SVM model we constructed proved to be suitable for discriminant analysis using this type of data, as the other models we employed in this study did not achieve the desired accuracy rates.…”
Section: Discussionmentioning
confidence: 99%
“…They achieved mixed results, yielding fair to excellent classification performances, with accuracy globally ranging from 60% to 97% [ 7 ]. A recent review assessing the application of digital tools for major depressive episodes described the following digital phenotype for BD: (1) speech alterations during a depressive episode, including decreased speech pause and reduced fundamental frequency, while these speech features were increased during a hypomanic episode; (2) irrespective of the mood state, heart rate variability was reduced, but the change in heart rate variability in the interepisodic phases remained unclear, and (3) an electrodermal hypoactivity in a depressive episode was reported, which increased when patients were euthymic [ 20 ].…”
Section: Digital Phenotyping To Detect Mood Symptoms and Mood Episode...mentioning
confidence: 99%